Impact of COVID-19 pandemic on biodiversity conservation in the Israeli occupied West Bank, Palestine - Qumsiyeh, Mazin B.; Abusarhan, Mohammad (Africana Studia, 2022)
The impact of COVID-19 induced a reduction on human mobility and other activities on biodiversity which has received significant interest. The initial studies showed a mixed bag, such as reductions in the use of motor vehicles and airplanes, with a positive impact on greenhouse gas emissions while the increased flocking of populations to public parks and green areas had a negative impact on resident wildlife. We provide a first assessment of COVID-19 impact in Palestine through direct observations and a survey of 29 biodiversity experts. Our findings in this area showed that the tourism-dependent economy suffered but there was an increase in the use of green areas with damaging effects such as hunting and dumping of solid and liquid wastes. On the other hand, there was an increase in local food production efforts, which are environmentally friendly. Keywords: Environment conservation, COVID-19, sustainability, tourism.